Anti-microbial resistance and molecular characterization of Salmonella serovars from man and animals - SHEKHAR, CHANDRA; SINGH, S P (The Indian Journal of Animal Sciences, 2014)
Varied samples (1,132) comprising poultry meat (212), poultry eggs (49), poultry droppings (60), autopsied poultry tissues (60), pork (156), pig faeces (189), cattle dung (105), buffalo dung (103), sheep faeces (11), goat faeces (31), deer faeces (2) and human stool (154) were screened for isolation of Salmonella spp. Total 50 Salmonella isolates were recovered from samples, viz. poultry meat (2), poultry eggs (1), poultry droppings (6), autopsied poultry tissues (16), pork (2), pig faeces (9), cattle dung (6), buffalo dung (3), sheep faeces (4) and human stool (1). The recovered Salmonella isolates belonged to 10 different serovars with most prevalent serovar S. Typhimurium (21) followed by S. Weltevreden (12), S. Ughelli (5), S. Essen (3), S. Elisabethville (2), S. Lagos (2), S. Drogana (2), S. Enteritidis (1), S. London (1) and un-typable Salmonella (1). Salmonella isolates showed extreme variation in resistance (0–100%) against anti-microbial agents. The maximum resistance was observed among Salmonella isolates against sulphamethizole and furazolidone (100% each) followed by kanamycin (50%), gentamicin (44%), nalidixic acid (14%), tobramycin (10%), amikacin, ampicillin, streptomycin and tetracycline (8% each), amoxicillin/ clavulanic acid (6%), norfloxacin (4%), ciprofloxacin and cefotaxime (2% each) and chloramphenicol (0%). A high level of sensitivity in Salmonella isolates was observed against chloramphenicol (100%) and tetracycline (92%). A high multiple antibiotic resistance (MAR) index in a range of 0.133–0.666 was observed in Salmonella serovars. Molecular characterization of Salmonella was performed by targeting amplification of invA gene primer fragment for confirmation of Salmonella spp. in which all isolates were found positive for this gene. Moreover, this gene encodes virulence factor in Salmonella spp. which was exhibited by all Salmonella isolates of the present study.